Thalamostriatal System Controls the Acquisition, Performance, and Flexibility of Learning Behavior - Kato, Shigeki; Nishizawa, Kayo; Kobayashi, Kazuto (Frontiers in Systems Neuroscience, 2021)
The dorsal striatum (DS) is a key structure of the basal ganglia circuitry, which regulates various types of learning processes and flexible switching of behavior. Intralaminar thalamic nuclei (ILNs) provide the main source of thalamostriatal inputs to the DS and constitute multiple nuclear groups, each of which innervates specific subdivisions of the striatum. Although the anatomical and electrophysiological properties of thalamostriatal neurons have been previously characterized, the behavioral and physiological functions of these neurons remain unclarified. Two representative thalamostriatal cell groups in the parafascicular nucleus (PF) and central lateral nucleus (CL) are located in the caudal and rostral regions of the ILNs in rodents. Recently, the behavioral roles of these thalamostriatal cell groups have been investigated by the use of genetic and pharmacological manipulation techniques. In the current review, we summarize behavioral studies on thalamostriatal neurons, showing key roles of these neurons in different learning processes, such as the acquisition, performance, and flexibility of behavior.